Bacterial Diversity, Organic Acid, and Flavor Analysis of Dacha and Ercha Fermented Grains of Fen Flavor Baijiu - Xue, Yu’ang; Tang, Fengxian; Cai, Wenchao; Zhao, Xinxin; Song, Wen; Zhong, Ji’an; Liu, Zhongjun; Guo, Zhuang; Shan, Chunhui (Frontiers in Microbiology, 2022)
Fen flavor Baijiu needs two rounds of fermentation process, which will obtain Dacha after initial fermentation and Ercha after secondary fermentation. The quality of Baijiu is closely related to the microbes within fermented grains. However, the bacterial diversity in Dacha and Ercha fermented grains of Fen flavor Baijiu has not been reported. In the present study, the structure and diversity of bacteria communities within fermented grains of Fen flavor Baijiu was analyzed and evaluated using MiSeq platform's HTS with a sequencing target of the V3-V4 region of 16S rRNA gene. Through the analysis of physical and chemical indexes and electronic senses, the relationship between bacterial flora, organic acid, taste and aroma in fermented grains was clarified. The results indicated that Lactobacillus was the main bacteria in Dacha, the mean relative content was 97.53%. The bacteria within Ercha samples were Pseudomonas and Bacillus, mean relative content was 37.16% and 28.02% respectively. The diversity of bacterial communities in Ercha samples was significantly greater than that in Dacha samples. The correlation between Lactobacillus and organic acids, especially lactic acid, lead to the difference between Dacha and Ercha organic acids, which also made the pH value of Dacha lower and the sour taste significantly higher than Ercha. Lactobacillus was significantly positively correlated with a variety of aromas, which made Dacha the response value of aromas higher. In addition, Bacillus had a significant positive correlation with bitterness and aromatic compounds, which lead to a higher response value of bitterness in Ercha and made it mainly present aromatic aroma. This study provides some clues for in-depth analysis of the difference between different stages of Fen flavor Baijiu, and theoretical support for the standard production and improvement in quality of Fen flavor Baijiu in the future.